Peningkatan Hasil Belajar Tematik Terpadu Menggunakan Model Pembelajaran Kooperatif Tipe Think Pair Share di Kelas IV SD - Mardiyah, Atika; Rahmatina, Rahmatina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
This research purpose is to know increase the learning outcomes in integrated thematic used cooperative learning model of Think Pair Share(TPS) type in grades IV elementary school. This research is as a Classroom Action Research (CAR) which acted for two cycles. Each cycle consists of the step of Planning, Actuating, Observing, and Reflecting. The subjects of this  research is student IV Elementary School 19 ATTS Bukittinggi as many as 18 students. The sources of data are collected from the teacher and the student. The main data collection technique used are observation, tes and non tes. Data analysis used are qualitative and quantitative  data analysis. The result of this research showed that used of Cooperative Learning Model of  Think Pair Share (TPS) type can increase the learning outcomes in integrated thematic student of IV Elementary School 19 ATTS Bukittinggi.